Public policy :preferences and outcomes - Simon, Christopher A. (Routledge, 2017)
Built on the premise that all public policy is ultimately grounded in the philosophy of governance, Christopher A. Simon's second edition continues to approach policy by combining normative and empirical perspectives. This deeply revised second edition continues to expose students to the basis of preferences, policy-making processes, policy history, and current policy decisions and outcomes. Chapters conclude with a case studies engaging students in the application of their theoretical knowledge to the real world, and encouraging them to be informed and active citizens.